ASSESSMENT OF INSECT DIVERSITY (HEMIPTERA & COLEOPTERA) IN HIMAYAT SAGAR AND OSMAN SAGAR LAKES OF HYDERABAD TELANGANA. - Suprabha Panda, Dr. Deepa Jaiswal, Prof. Vanita Das, Prof. M. Madhavi (Chelonian Research Foundation, 2024)
This study investigates the diversity of Hemiptera and Coleoptera in Himayat Sagar and Osman Sagar lakes during monsoon 2023. We recorded a total of 47 species at each lake, with Himayat Sagar showing higher species richness and more even distribution compared to Osman Sagar. The Shannon-Wiener and Simpson’s indices were used to quantify diversity and evenness, revealing that Himayat Sagar supports a more balanced and diverse insect community. These findings highlight the impact of environmental conditions on insect populations and provide recommendations for conservation.